Bonded anchors with post-installed supplementary reinforcement under tension loading – Experimental investigations. (1st February 2022) - Vita, Norbert; Sharma, Akanshu; Hofmann, Jan
Highlights: Experiments on bonded anchors with post-installed supplementary reinforcement. Strong influence of post-installed reinforcement on behaviour of anchorages. For low amounts of reinforcement, yielding of reinforcing bars governs. For high amount of the reinforcement the failure load is governed by strut failure. Both the reinforcement and concrete contribute significantly towards the resistance. Abstract: This paper presents the results of comprehensive and systematic experimental investigations carried out on anchorages (single anchors and groups) of bonded anchors supplemented with post-installed reinforcement subjected to tension loading. Until now, the use of supplementary reinforcement is allowed in the codes only for anchorages with cast-in headed anchors supplemented with cast-in reinforcement. In this work, tension tests are performed on single anchors and anchor groups with different amounts and arrangements of post-installed reinforcement. Epoxy based mortar was used for installation of both anchors and the reinforcement. It was found that the post-installed supplementary reinforcement can significantly increase the capacity of anchorages undergoing concrete cone breakout failure. Due to high bond strength of the mortar, even relatively short bond lengths within the breakout body were sufficient to activate the reinforcement and contribute significantly towards the resistance. The ultimate load was limited either by reinforcement yielding (for low amounts of reinforcement) or strut failure (for moderate to high amounts of reinforcement). Not just the amount but also the placement and arrangement of reinforcement plays an important role in the tension behavior of anchorages with post-installed supplementary reinforcement. At peak load, both the concrete as well as reinforcement contribute significantly to the resistance of the anchorage.